2016
DOI: 10.1103/physrevb.94.144424
|View full text |Cite
|
Sign up to set email alerts
|

Scaling study and thermodynamic properties of the cubic helimagnet FeGe

Abstract: The critical behavior of the cubic helimagnet FeGe was obtained from isothermal magnetization data in very close vicinity of the ordering temperature. A thorough and consistent scaling analysis of these data revealed the critical exponents β = 0.368, γ = 1.382, and δ = 4.787. The anomaly in the specific heat associated with the magnetic ordering can be well described by the critical exponent α = −0.133. The values of these exponents corroborate that the magnetic phase transition in FeGe belongs to the isotropi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
9
31
0
Order By: Relevance
“…Using high sensitivity Hall Effect measurements in FeGe crystals, we observe a skyrmion THE of amplitude +5 n .cm at 276 K (3°C). This THE coincides with the skyrmion lattice phase identified by small angle neutron scattering 42 , and its amplitude is as large as the THE observed in MnSi at 29 K. Adjacent to the skyrmion phase, we also observe the signature of a magnetic phase that is not present in the prototypical skyrmion compound MnSi, and merges into the inhomogeneous chiral spin state 51 . Finally, comparing THE in MnSi and FeGe we emphasise the quantitative and qualitative failings of the formula that is generally used to estimate the skyrmion THE.…”
Section: Introductionsupporting
confidence: 81%
“…Using high sensitivity Hall Effect measurements in FeGe crystals, we observe a skyrmion THE of amplitude +5 n .cm at 276 K (3°C). This THE coincides with the skyrmion lattice phase identified by small angle neutron scattering 42 , and its amplitude is as large as the THE observed in MnSi at 29 K. Adjacent to the skyrmion phase, we also observe the signature of a magnetic phase that is not present in the prototypical skyrmion compound MnSi, and merges into the inhomogeneous chiral spin state 51 . Finally, comparing THE in MnSi and FeGe we emphasise the quantitative and qualitative failings of the formula that is generally used to estimate the skyrmion THE.…”
Section: Introductionsupporting
confidence: 81%
“…During the last years, the precursor states of noncentrosymmetric ferromagnets have been investigated experimentally and theoretically [14][15][16][17][18][19][20][21][22][23]. Particularly, the recent observations in bulk cubic helimagnets MnSi [18] and FeGe [16][17][18] are consistent with the crossover effects of skyrmionic states theoretically described in [9][10][11] and earlier reported in a cubic helimagnet FeGe [10,11].…”
Section: Introductionsupporting
confidence: 74%
“…Fisher and Langer [59] showed that in the case of short-range interactions, the derivative of the resistivity dρ xx /dT should vary as the magnetic specific heat, which has been seen to be the case in MnSi [60,61]. While FeGe shows a conventional cusp in the specific heat [62], there is no corresponding peak in dρ xx /dT here or in previous work on thin films [32,33]. An alternative theoretical approach is to look at the long-range interaction contribution, which has been used to describe the resistivity anomalies found in periodic magnetic structures, with spin-spiral rare-earth systems given as an example [63].…”
Section: Resistivity and Magnetoresistancementioning
confidence: 96%